2006
DOI: 10.4049/jimmunol.177.2.1240
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia Endosymbiotic Bacteria of Brugia malayi Mediate Macrophage Tolerance to TLR- and CD40-Specific Stimuli in a MyD88/TLR2-Dependent Manner

Abstract: Lymphatic filarial nematodes are able to down-regulate parasite-specific and nonspecific responses of lymphocytes and APC. Lymphatic filariae are reliant on Wolbachia endosymbiotic bacteria for development and survival. We tested the hypothesis that repeated exposure to Wolbachia endosymbionts would drive macrophage tolerance in vitro and in vivo. We pre-exposed murine peritoneal-elicited macrophages to soluble extracts of Brugia malayi female worms (BMFE) before restimulating with BMFE or TLR agonists. BMFE t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 43 publications
6
71
0
Order By: Relevance
“…Oral MIN administration in infected SCID mice for 28 days reduced Wolbachia loads within female Bm below the 90% threshold deemed to irreversibly sterilise filarial tissues in clinical studies, leading to macrofilaricidal effects [33,42,43]. The >90% levels of depletion observed in female macrofilariae derived from drugged SCID Bm infections were consistent with in vivo effects reported following protracted tetracycline treatments in patent Bm infections of gerbils [44] and were reflected in a complete blockade in mf release in drugged animals. Having validated the SCID model system as suitably responsive to a range of filaricidal reference compounds, we tested survival rates of male Onchocerca macrofilariae in either SCID BALB/c or WT BALB/c mice.…”
Section: Discussionsupporting
confidence: 70%
“…Oral MIN administration in infected SCID mice for 28 days reduced Wolbachia loads within female Bm below the 90% threshold deemed to irreversibly sterilise filarial tissues in clinical studies, leading to macrofilaricidal effects [33,42,43]. The >90% levels of depletion observed in female macrofilariae derived from drugged SCID Bm infections were consistent with in vivo effects reported following protracted tetracycline treatments in patent Bm infections of gerbils [44] and were reflected in a complete blockade in mf release in drugged animals. Having validated the SCID model system as suitably responsive to a range of filaricidal reference compounds, we tested survival rates of male Onchocerca macrofilariae in either SCID BALB/c or WT BALB/c mice.…”
Section: Discussionsupporting
confidence: 70%
“…The role of potential anti-inflammatory factors released by the filaria and the role of adaptive host responses are not addressed in this study and potentially add to the complexity of the pathogenesis of filarial diseases. Turner et al (68) have recently shown that immune tolerance induced by Wolbachia containing Brugia extracts to a range of TLR ligands is dependent on TLR2 and MyD88 but not TLR4. In our recent study of O. volvulus induced neutrophil recruitment in the cornea, Wolbachia-induced production of proinflammatory and chemotactic cytokines, development of corneal haze, and neutrophil activation were completely abrogated in MyD88 Ϫ/Ϫ mice (27), consistent with the data presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the protective effects that prepatent female adult worms had on LPS challenge is the release of helminth products that directly impede the immune response triggered by LPS, as earlier studies have demonstrated that helminths can secrete products that reduce the responses of Toll-like receptors (TLRs) to LPS. Soluble extracts from Brugia malayi and Schistosoma mansoni reduced the TLR4 expression on macrophages and the ability of TLRs from dendritic cells to respond to LPS (21,31,38). Further studies with female adult L. sigmodontis worms will investigate these possible protective mechanisms with respect to LPS-induced sepsis.…”
Section: Resultsmentioning
confidence: 99%